The Bog Find from Sigersdal: Human Sacrifice in the Early Neolithic - Bennikke, Pia; Ebbesen, Klaus (Journal of Danish Archaeology, 1986)
The Bog Find from Sigersdal: Human Sacrifice in the Early Neolithic